Genetic Counselors' and Genetic Counseling Students' Attitudes Around the Clinical Doctorate and Other Advanced Educational Options for Genetic Counselors: A Report from the Genetic Counseling Advanced Degree Task Force. Issue 4 (30th October 2014) - Nagy, Rebecca; Peay, Holly; Hicks, Melissa; Kloos, Jacqueline; Westman, Rachel; Conway, Laura; Finucane, Brenda; Fitzpatrick, Jennifer; Gordon, Erynn; Ramos, Erica; Sekhon‐Warren, Jaspreet; Silver, Josh; et al.
Abstract: Since its establishment over 40 years ago, the genetic counseling profession has grown to an estimated ~4, 000 professionals in North America. While the profession has maintained the Master's degree as the entry‐level and terminal degree, many other allied health professions have added advanced training pathways, such as the clinical doctorate (ClinD) either as an optional post‐professional degree or required entry‐level degree. Discussions regarding advanced degrees have also occurred within the genetic counseling profession, dating back to as early as the 1980s. In 2011, the Genetic Counseling Advanced Degree Task Force (GCADTF) was convened to explore the issue again, with the goal of "[engaging] all of the professional leadership organizations in the field of genetic counseling in a decision‐making process about whether the profession should move to a Clinical Doctorate". As part of their work, the GCADTF surveyed practicing genetic counselors ( n  = 4, 321) and genetic counseling students ( n  = 522) in the US and Canada regarding their interest in moving to the ClinD as the entry‐level degree. This survey also included questions about other options for advanced training to generate data to inform future discussions around this very important professional issue. Herein, we describe the results of the survey, with particular attention to genetic counselor preferences for additional advanced education/certification opportunities and recommendations for future discussion.